2012
DOI: 10.1007/s00125-012-2562-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell signalling in insulin secretion: the molecular targets of ATP, cAMP and sulfonylurea

Abstract: Clarification of the molecular mechanisms of insulin secretion is crucial for understanding the pathogenesis and pathophysiology of diabetes and for development of novel therapeutic strategies for the disease. Insulin secretion is regulated by various intracellular signals generated by nutrients and hormonal and neural inputs. In addition, a variety of glucose-lowering drugs including sulfonylureas, glinide-derivatives, and incretin-related drugs such as dipeptidyl peptidase IV (DPP-4) inhibitors and glucagon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 109 publications
5
109
1
Order By: Relevance
“…It is likely that TRPM2 is regulated by EPAC in our study. Interaction of sulfonylurea receptor 1/EPAC2A protein-protein (27)(28)(29) and increased EPAC2A activity by sulfonylureas (30) has been reported. PKA-independent potentiation of insulin secretion by cAMP (presumably EPAC2A-dependent pathway) was attenuated in sulfonylurea receptor 1-deficient islets (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that TRPM2 is regulated by EPAC in our study. Interaction of sulfonylurea receptor 1/EPAC2A protein-protein (27)(28)(29) and increased EPAC2A activity by sulfonylureas (30) has been reported. PKA-independent potentiation of insulin secretion by cAMP (presumably EPAC2A-dependent pathway) was attenuated in sulfonylurea receptor 1-deficient islets (31).…”
Section: Discussionmentioning
confidence: 99%
“…Its chemical formula can be seen in Figure 2. Their mechanism of action is to trigger insulin release from pancreatic b-cells 45 In addition can decrease the hepatic glucose production and the uptake of hepatic insulin while can increase the glucagon secretion by pancreatic α-cells 5 The main drawback of SU is that can induce hypoglycemia due to the excess of insulin production and release. First generation drugs include acetohexamide, carbutamide, chlorpropamide, glycyclamide (tolhexamide), metahexamide, tolazamide and tolbutamide while as second generation drugs classified glibenclamide (glyburide), glibornuride, gliclazide, glipizide, gliquidone, glisoxepide and glyclopyramide.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…Stimulation of the secretion of glucagon, but not insulin, by adenosine suggested that α-cells were more sensitive to adenosine than β-cells [330]. There have been some valuable reviews about various aspects of purinergic endocrine signalling in the pancreas over the years [50,66,133,219,228,337,382,411,479,515,524]. A recent one is available about purinergic signalling in diabetes ([67]; Fig.…”
Section: Pancreasmentioning
confidence: 99%
“…ATP increases [Ca 2+ ] i in clonal insulin-producing RINm5F cells [15]. ATP action was found to be glucose-dependent and was exerted via two different types of P2 receptors: P2X receptors on rat pancreatic β-cells transiently stimulated insulin release at low glucose concentrations and P2Y receptors potentiated glucose-stimulated insulin secretion ( [410]; see [479]). Electrophysiological and immunocytochemical evidence has been presented that P2X1 and P2X3 receptors are expressed by mouse pancreatic β-cells [484].…”
Section: β-Cellsmentioning
confidence: 99%